2020
DOI: 10.1042/bst20200666
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted roles of long non-coding RNAs in triple-negative breast cancer: biology and clinical applications

Abstract: Triple-negative breast cancer (TNBC) is a heterogeneous breast cancer subtype that lacks targeted therapy due to the absence of estrogen, progesterone, and HER2 receptors. Moreover, TNBC was shown to have a poor prognosis, since it involves aggressive phenotypes that confer significant hindrance to therapeutic treatments. Recent state-of-the-art sequencing technologies have shed light on several long non-coding RNAs (lncRNAs), previously thought to have no biological function and were considered as genomic jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 166 publications
0
4
0
Order By: Relevance
“…Nanocarriers are being explored as versatile delivery systems to enhance therapeutic agents' specificity and efficacy. [65] Current methods have limitations, and nanotherapeutic-based platforms are being investigated. A bio-scaffold containing lncRNA-targeting biomimetic nanostructures was created to modulate immune responses against colorectal cancer recurrence after surgery.…”
Section: Targeting Lncrnas For Therapeutic Applications; Nanocarriers...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocarriers are being explored as versatile delivery systems to enhance therapeutic agents' specificity and efficacy. [65] Current methods have limitations, and nanotherapeutic-based platforms are being investigated. A bio-scaffold containing lncRNA-targeting biomimetic nanostructures was created to modulate immune responses against colorectal cancer recurrence after surgery.…”
Section: Targeting Lncrnas For Therapeutic Applications; Nanocarriers...mentioning
confidence: 99%
“… [23] However, effective delivery remains a challenge. Nanocarriers are being explored as versatile delivery systems to enhance therapeutic agents′ specificity and efficacy [65] . Current methods have limitations, and nanotherapeutic‐based platforms are being investigated.…”
Section: Targeting Lncrnas For Therapeutic Applications; Nanocarriers...mentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a new class of stem cell regulators that play important roles in a wide range of cellular processes [ 15 ]. Studies employing powerful new technologies and bioinformatics tools have identified lncRNAs (with greater than 200 nucleotides in length) that can regulate oncogene expression by binding to chromatin-modifying factors and transcription factors or altering the splicing, stability, or translation of mRNAs [ 16 , 17 , 18 , 19 ]. The expression patterns and functions of lncRNAs are highly cell-type specific.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has revealed the enormous promise for miRNAs to improve the diagnosis, and management of all major gynecological cancers (cervical, endometrial and ovarian cancers) [1]. This is backed up by research on miRNAs in other cancers such as thyroid, breast and gastric cancer [13][14][15]. Numerous miRNAs are believed to influence multiple biological functions, leading to modulation of the tumor microenvironment, including stemness, growth, proliferation, invasion and metastasis [1].…”
Section: Introductionmentioning
confidence: 99%